Exploring the Fascinating Diversity, Medicinal Significance, and Ecological Adaptation of Ceropegia bulbosa Roxb.: A Comprehensive Review - Chothani, Daya L.; Trivedi, Udit; Patel, Jigneshkumar I. (Current Traditional Medicine, 2025)
A large variety of unknown plants has tremendous usefulness in improving human beings from a medicinal, nutritional, and dietary perspective. Ceropegia bulbosa species are threatened plant species by (the International Union for Conservation of Nature) IUCN which have significant medicinal value. Ceropegia bulbosa species are generally found in various regions of India. GC-MS data of different extracts such as Ethanol, Methanol, Acetone, Ethyl acetate, and chloroform show the biologically active compounds that exhibit various biological actions. Bioactive compounds reported in Ceropegia bulbosa are Tetradecanoic acid, Pentadecanoic acid, Heptadecanoic acid, Octadecanoic acid, Ergost-5-en-3-ol, (3 beta, 24R)-Stigmast-5-en-3-ol, Tetracontane, Squalene, Beta-stigmasterol.Traditionally, leaves, tubers, stems, and flowers are used in the treatment of several diseases. Also, various tribal and rural regions have a different identity of Ceropegia bulbosa. Hence, it has the same ethnopharmacological remedies like the decoction of tubers used to treat dysentery and diarrhea and remove kidney stones. Pulp of leaves used for deafness.Traditionally, it is used as an anti-urolithic, dysentery and diarrhea, deafness, and fertility enhancer. The plant is reported as anti-urolithic, anti-fungal, anti-oxidant, immunomodulatory, malnutrition, and Balya karma. Ceropegia bulbosa is reported to contain Tetradecanoic acid, Pentadecanoic acid, Heptadecanoic acid, Octadecanoic acid, Ergost-5-en-3-ol, (3 beta, 24R)-Stigmast-5-en-3-ol, Tetracontane, Squalene, Beta-stigmasterol.
Keywords: morphology